Respuesta :
Step 1: Simplify both sides of the equation.
18x−5=3(6x−2)18x+−5=(3)(6x)+(3)(−2)(Distribute)18x+−5=18x+−618x−5=18x−6Step 2: Subtract 18x from both sides.18x−5−18x=18x−6−18x−5=−6Step 3: Add 5 to both sides.−5+5=−6+50=−1Answer:There are no solutions.
18x−5=3(6x−2)18x+−5=(3)(6x)+(3)(−2)(Distribute)18x+−5=18x+−618x−5=18x−6Step 2: Subtract 18x from both sides.18x−5−18x=18x−6−18x−5=−6Step 3: Add 5 to both sides.−5+5=−6+50=−1Answer:There are no solutions.
18x - 5 = 3(6x-2)
Open parenthesis and distribute
18x - 5 = 18x - 6
Subtract both sides by 18x
-5 = -6
Since -5 does not equal -6, there is no value of x that will work in the equation.
Open parenthesis and distribute
18x - 5 = 18x - 6
Subtract both sides by 18x
-5 = -6
Since -5 does not equal -6, there is no value of x that will work in the equation.